Ant-based approach for dynamic difficulty adaptation in post-stroke therapeutic games - Gouaïch, A.; Hocine, N. (International Journal of Computer Science in Sport, 2012)
Post-stroke therapeutic games can be considered as a promising rehabilitation tool since they provide personalized rehabilitation sessions in which training intensity and challenge can be manipulated and adapted to each patient. In this short paper, we describe an adaptation framework dedicated to pointing games. This approach has been implemented and tested with the RehabCraft game as a case study. Besides, we describe an on-going experimental evaluation of the proposed framework.